Sistem Informasi Online pada Direktorat Tahanan dan Barang Bukti Polda Sumatera Barat dengan Menggunakan Bahasa Pemrograman PHP MYSQL - Ahmad Junaidi (INTECOMS: Journal of Information Technology and Computer Science, 2018)
The rapid development of science and technology has encouraged humans to find and implement new methods or methods in monitoring and controlling data processing systems so that they can run smoothly. The ability and speed of computers in processing data over and over again and with very large amounts is no doubt to produce reports needed in the strategic decision making process. So that at this time many companies and government agencies are using computer technology to help solve their data processing problems. This study aims to review the extent of existing procedures and can present information reports obtained. And develop a new information system by further refining the old system to achieve work efficiency. At the Directorate of Detention and Evidence (DITTAHTI) of the West Sumatra Regional Police, the processing of prisoner data and items of evidence has often been carried out, but has not yet obtained optimal results. This is due to the use of information technology that is still lacking and is still being implemented offline and manually by the municipal and district police. Optimization of data processing is needed so that the integrity, access rights and availability of data can be maintained properly. Application system that will be proposed later is PHP MYSQL. All data entry will be processed in a Database. Varied data will be more easily and quickly processed in a well-organized system. Keywords: Information Systems, Directorate of Detention and Evidence, PHP, MYSQL